Model of goal directed behavior for limiting Latino preschoolers' television viewing: validity and reliability - Marissa Ogren; Tom Baranowski; Sarah J. Lowry; Jason A. Mendoza (BMC, 2020)
Abstract Background Accurately measuring parents' attitudes and beliefs regarding limiting their children's TV viewing is important to inform the design and evaluation of effective interventions. This manuscript assesses the internal consistency reliability, test-retest reliability, convergent validity, and construct validity of the Model of Goal Directed Behavior (MGDB) scales among parents of Latino preschoolers to characterize Latino parents' attitudes and beliefs toward limiting their preschoolers' TV viewing. Method Participants included parents of Latino preschoolers in the United States, 3-5 years old (n = 186). Parents completed a socio-demographic survey and the 105-item MGDB questionnaire (Attitudes, Perceived Positive/Negative Behavioral Control, Subjective Norms, Positive and Negative Anticipated Emotions, Habits, Self-Efficacy, Desires, and Intentions surrounding their child's TV viewing) which was used to measure internal consistency reliability and construct validity. A subsample of participants completed the questionnaire twice to measure test-retest reliability. Further, parents completed a 7-day TV viewing diary for their preschooler, and a TV parenting practices questionnaire as measures of convergent validity. Results Internal consistency reliability was generally acceptable for the MGDB scales (Cronbach's alphas> 0.7), except for the Desires scale, which was revealed to have two factors and the Attitudes and Perceived Behavioral Control scales. Test-retest reliability over 2 months had negligible to moderate correlations (r's = 0.28 to 0.61). Two structural equation models were conducted. One yielded acceptable model fit (x 2 (97) = 113.65, p = .119) and the other had questionable model fit (x 2 (97) = 125.39; p = .028). Testing convergent validity, only two MGDB scales (Habits and Self-Efficacy) were positively correlated with the TV parenting practices questionnaire (r's = 0.33 to 0.51), and none were meaningfully correlated with preschoolers' mean daily TV viewing. Conclusions Initial reliability and validity for some of the MGDB scales appear acceptable among parents of Latino preschoolers. Refinement of the instrument and testing among larger samples is necessary to fully evaluate psychometric properties. This instrument may be useful for characterizing Latino parents' attitudes and beliefs toward limiting their preschoolers' TV viewing and informing future TV reduction interventions. Trial registration Clinical Trials NCT01216306 Registered October 6, 2010.